2017
DOI: 10.1093/mnras/stx3194
|View full text |Cite
|
Sign up to set email alerts
|

SN 2014C: VLBI images of a supernova interacting with a circumstellar shell

Abstract: We report on VLBI measurements of supernova 2014C at several epochs between t = 384 and 1057 days after the explosion. SN 2014C was an unusual supernova that initially had Type Ib optical spectrum, but after t = 130 d it developed a Type IIn spectrum with prominent Hα lines, suggesting the onset of strong circumstellar interaction. Our first VLBI observation was at t = 384 d, and we find that the outer radius of SN 2014C was (6.40 ± 0.26) × 10 16 cm (for a distance of 15.1 Mpc), implying an average expansion v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 30 publications
7
40
1
Order By: Relevance
“…This is roughly consistent with the deceleration observed in the ejecta. The "b" component of the spectral profile may arise from the same hot spot found in the VLBI imaging (Bietenholz et al 2018).…”
Section: Light Curve Modelingmentioning
confidence: 78%
See 1 more Smart Citation
“…This is roughly consistent with the deceleration observed in the ejecta. The "b" component of the spectral profile may arise from the same hot spot found in the VLBI imaging (Bietenholz et al 2018).…”
Section: Light Curve Modelingmentioning
confidence: 78%
“…The shock front (v ≈ 10000 km s −1 ) would already be at 10 17 cm at that epoch, indicating that the CSM shell was more extended than previously thought. With a prolonged interaction with such dense medium, one might expect the forward shock of the SN to substantially slow down, but the radio imaging of the SN using very long baseline interferometry (VLBI) showed that the velocity of the shock barely decreased during the first 1000 days (Bietenholz et al 2018). They also showed in the resolved VLBI image at 1057 days that the CSM was likely asymmetric.…”
mentioning
confidence: 99%
“…Most notable is the remarkable SN 1987A, for which a complex CSM ring was directly imaged (e.g., Jakobsen et al 1991;Panagia et al 1991). Others include, e.g., SNe 1979C, 1986J, 1997eg, 1998S, 1993J, 2005kd, 2006jc, 2006gy, 2008iz, 2010jl, 2011dh, and 2014C (e.g., Leonard et al 2000Smith et al 2007;Foley et al 2007;Hoffman et al 2008;Chandra et al 2009b;Bietenholz et al 2010;Martí-Vidal et al 2011;Bietenholz et al 2012;Katsuda et al 2016;Kimani et al 2016;Dwarkadas et al 2016;Bartel et al 2017;Bietenholz et al 2018), many of which are classified as type IIn.…”
Section: Line Structurementioning
confidence: 99%
“…It was classified as a hydrogen-poor Type Ib SN (Kim et al 2014) indicating a mass loss before its explosion. Over the course of one year, it evolved into an Hα emission prominent type IIn SN implying its interaction with nearby circumstellar shell (Milisavljevic et al 2015;Margutti et al 2017;Bietenholz et al 2018). A series of Chandra observations was proposed after the explosion of SN 2014C, which provide multiple observations of NGC 7331 in X-ray.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Chandra and NuSTAR data, we obtained the X-ray light curve of SN 2014 by fitting a tbabs*apec model in 0.3 -30 keV, the variation of column density, the plasma temperature and the photon indexes.The close and open circles represent the unabsorbed and absorbed luminosities respectively. Based on 8.4 GHz VLBI data of SN 2014C, the measured denstiy fluxes and the fitted angular outer radius of a spherical shell model estimated inBietenholz et al (2018) are also plotted for reference. All the errors are at 90% confidence level.…”
mentioning
confidence: 99%